The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/ctpp.201010152
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Channel Analyzer Investigations of Ion Flux at the Target Surface in Pilot‐PSI

Abstract: Pilot-PSI is a linear plasma device designed for investigations of plasma-surface interaction. A cascaded-arc plasma source operated in argon or/and hydrogen generates a high-density plasma that is magnetically confined on the vessel's axis, resulting a plasma column of about 1-2 cm in diameter which interacts with a solid target. A multi-channel analyzer was constructed to study the radial distribution of the ion flux at the target surface. The analyzer was placed in the centre of Pilot-PSI target and current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…At target position, the magnetic confinement of the plasma can be considered rather weak, since the cyclotron frequency of H + ions is in the same range as their collision frequency, but this doesn't limit the validity of the results. Similar distributions were also obtained at higher magnetic fields, both in Magnum-PSI [3] as well as in Pilot-PSI [4]. Moreover, the radial gradient of the floating potential is larger for higher magnetic field strengths [3].…”
Section: Current Distribution To the Surface Of The Floating Targetsupporting
confidence: 78%
“…At target position, the magnetic confinement of the plasma can be considered rather weak, since the cyclotron frequency of H + ions is in the same range as their collision frequency, but this doesn't limit the validity of the results. Similar distributions were also obtained at higher magnetic fields, both in Magnum-PSI [3] as well as in Pilot-PSI [4]. Moreover, the radial gradient of the floating potential is larger for higher magnetic field strengths [3].…”
Section: Current Distribution To the Surface Of The Floating Targetsupporting
confidence: 78%
“…The plasma beam in Magnum-PSI has so far mainly been characterized using Thomson scattering (TS) [4] and optical emission spectroscopy (OES) while the target surface has been investigated using infra-red (IR) imaging and calorimetry [5]. However, it has been shown that in Pilot-PSI-the forerunner of Magnum-PSI-the plasma beam is characterized by a strong radial electric field [6,7] and radial current flows through the sample exposed to the plasma [7]. It is thus of interest to characterize those parameters in Magnum-PSI where the target is exposed in a diverging magnetic field region.…”
Section: Introductionmentioning
confidence: 99%